The highlander's forbidden bride eaudiobook - Fletcher, Donna (Sinclare Brothers, 2020)
Donna Fetcher's The Highlander's Forbidden Bride is the thrilling conclusion of this exceptional storyteller's series featuring the rugged, proud, and sexy Scotsmen, the Sinclare brothers. Evocatively set in the Highlands of Scotland, this powerful and stirring tale of vengeance turned to lust and hatred undone by passion is yet another breathtaking example of what bestseller Patricia Potter calls Fletcher's "pure magic." If you like the manly heroes and strong, sensual heroines of New York Times bestselling author Catherine Coulter, you'll love Donna Fletcher—and especially The Highlander's Forbidden Bride !